AI in literature research: a workshop perspective (Journal of EAHIL, 2025)
Artificial intelligence (AI) is increasingly used in academic research, including literature search and systematic reviews. This article shares insights from the “AI in Literature Research” workshop held at the 2025 VOGIN-IP-lezing in Amsterdam. The workshop, attended by 45 information professionals, included a poll, a theoretical session on AI tools, and a hands-on session exploring AI search tools (Perplexity, SciSpace, and Elicit). Participants were generally positive about AI developments but also raised concerns about transparency, reliability, and bias. The workshop enabled information professionals to explore tools, exchange perspectives and reflect on the role of AI in literature research and research support.